Computational Approaches to Exploring Persian-Accented English - Miller, Corey (Research in Language, 2015)
Methods involving phonetic speech recognition are discussed for detecting Persianaccented English. These methods offer promise for both the identification and mitigation of L2 pronunciation errors. Pronunciation errors, both segmental and suprasegmental, particular to Persian speakers of English are discussed.